Going left or right? A study of the policy rationale of the Chilean center-left coalition Concertación in Education - Falabella, Alejandra (Education Policy Analysis Archives, 2021)
What does it mean to deliver left-wing policies in education nowadays? During most of the 20th century, political parties of the center-left traditionally fought for a welfare state and a comprehensive public education. However, in an era of advanced capitalism, these same parties have tended to advocate and even deepen neoliberal and new public management reforms. In Chile, the center-left “Concertación” coalition governed for 20 years (1990-2010), inheriting a market-driven educational system established under the dictatorship of Augusto Pinochet. This paper, based on an analysis of official public speeches and documents (in total 62), examines the Concertación’s rationale and political project in school education. The coalition’s aim was to move from a “free market” to a regulated market, through a balanced formula that—while preserving the market framework—added greater state investment, compensatory programs, and performance accountability measures. Hypotheses circulated in the country that the Concertación did not deliver further transformations due to legal constraints, international pressure, and “conflict phobia”. Despite historical limitations and internal disputes, the research provides evidence that the government’s educational program, in large part, was true to its own system of thinking. Hence, the center-left coalition did not maintain the market-based model in spite of its governmental rationality, but because of it.